Peningkatan Mutu Wasit Dan Juri Kabaddi Di Wilayah Berau Menuju Porprov VII Berau, Provinsi Kalimantan Timur - Januar Abdilah Santoso; Julianur Julianur; Nanda Alfian Mahardhika; Jeane Betty Kurnia Jusuf (Jurnal Dharma Pendidikan dan Keolahragaan, 2022)
This community service activity is an effort to improve the quality of referees and judges for the kabaddi sport in the Berau region as the host of Porprov VII in East Kalimantan. The objectives of this community service activity in detail are as follows: (1) As a means of socialization, education and training for Kabaddi sports in accordance with IKF regulations, (2) As a means of improving the quality of human resources for match equipment. The location of the activity is in the district of Berau, East Kalimantan. The plan for the training participants is 15 people to minimize the gathering of too many people. The service method uses training methods which include lectures to convey basic theory and practice to apply theoretical understanding in the field and evaluation to see quality improvements after participating in activities. The result that has been achieved from this activity is the increase in the quality of Match Equipment Resources. Indicators of success can be seen from the increase in general knowledge about Kabaddi, Kabaddi match rules and participants are able to organize Kabaddi matches independently.